Understanding the stability of Samanea saman trees through tree pulling, analytical calculations and numerical models - Rahardjo, H. (2014)
There have been several cases of tree failure in Singapore. Many studies have shown that soil properties and root architecture of trees are important factors that govern tree stability. Twenty Samanea saman trees were planted in different soil media, which were original in-situ soil, top soil, mixture of 50% granite chips and 50% top soil, and mixture of 80% granite chips and 20% top soil. The objectives of this study were to investigate tree overturning processes and also to compare the results of tree pulling tests with results from an analytical calculation and numerical modeling for different soil types. The results showed that stability of the trees were not governed by the shear strength of the soil. Factors that affected tree stability included cross-sectional area of the roots and root plate area. Tree pulling test and numerical modeling results showed that there were two modes of failure which occurred when a tree was overturned. The first mode was the shear failure of soil and the second was a combination of shear failure of soil and root breakage. The maximum overturning force obtained from the tree pulling test was in the same order of magnitude as the maximum overturning forces obtained from the analytical calculation and numerical modeling.